A study on planning of childcare centre in neighbourhood area: case study of Bandar Bukit Tinggi, Klang, Malaysia - Bahrom, Atkah Salwa; Abdullah, Alias (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2005)
The study attempts to reveal scenario of childcare centres operating in the neighbourhood area. Presently, the operation of childcare centres in residential units has become a trend in urban areas. Consequently, activities of childcare centres create unwanted circumstances. This study takes two-prong approach to the issue of providing well-planned space for childcare centres. It is based on the review of various guidelines on philosophical and psychological development of children and on what constitute a good design and planning of childcare centres. Several techniques of analysis have been applied, which include a comparative study, survey technique, and observation. Two residential areas have been selected as case studies. The objectives of the study are: (l) to study the various standards and guidelines of childcare centres from relevant sources in terms of its implementation, acceptance and usage that suit the local condition, (2) to test lists of criteria for planning the ideal childcare centres, (3) to identify issues and problems of childcare centre within the study area, (4) to analyze the findings by using appropriate methods such as comparative study, (5) survey technique and observation, (6) to recommend a new amendment of guidelines based on the criteria listed for the future planning of childcare centres in Malaysia. A survey has been done to collect local people's perceptions of the childcare centre and how far they have benefited from it. The findings of this study reveal that most of the childcare centres remains at very minimum standard of criteria that have been outlined in the existing guidelines. This study recommends improvement and additional guideline to improve the present childcare centres.